Pacing strategy and workload distribution as determinants of success in one-day monument cycling races - Sánchez-Jiménez, J. L.; Javaloyes, A.; Peña-González, I.; Moya-Ramón, M.; Mateo-March, M. (The Journal of Strength and Conditioning Research, 2026)
This study examines workload distribution and pacing strategies in professional cyclists who finished in the top 5 compared with those ranked 6th-30th in Monument races. Power output data from 30 professional male cyclists and a total of 42 race files were analyzed across Milan-San Remo, the Tour of Flanders, Paris-Roubaix, Liège-Bastogne-Liège, and Il Lombardia (2021-2023), which are the 5 most prestigious 1-day "Monument" races in professional cycling. Top-5 cyclists exhibited a lower-body mass index (p = 0.021) and a higher compound score (p = 0.034) than top 6-30 finishers. A repeated-measures ANOVA showed significant differences in accumulated workload across power zones (p < 0.001), with zone 4 being the only zone where top-5 cyclists significantly outperformed others (p = 0.017; ES = 0.7). In addition, top-5 cyclists expended significantly more energy in zone 4 during the third quarter of the race (p = 0.022), suggesting greater fatigue resistance. A multiple discriminant analysis confirmed zone 4 workload as the primary predictor distinguishing between groups (Lambda = 0.896; p = 0.037), correctly classifying 71.2% of cases. These findings highlight the role of submaximal endurance and physiological durability in Monument race success. Differences in pacing strategies, particularly the ability to sustain higher zone 4 efforts in decisive race phases, may be key to achieving top performance.